2017
DOI: 10.1007/s12328-017-0732-5
|View full text |Cite
|
Sign up to set email alerts
|

Significance of genetic polymorphisms in patients with nonalcoholic fatty liver disease

Abstract: Because of recent advances in genetic research such as genome-wide association studies, the underlying genetic mechanisms of nonalcoholic fatty liver disease (NAFLD) pathophysiology have been elucidated. Here, we present a review of the current literature on the impact of genetic polymorphisms in patients with NAFLD. These genetic polymorphisms, which regulate lipid metabolism, glucose metabolism, and the renin-angiotensin system, are involved in NAFLD onset, steatosis, inflammation, fibrosis, and hepatocellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 65 publications
1
11
1
5
Order By: Relevance
“…Our finding is in agreement with Bernard et al; Hussain et al; Peng et al; Zheng et al; Miyaaki and Nakao who reported that MTP -493G/T polymorphism may be used for early detection of NAFLD. 16 , 12 , 2 , 36 , 37 This might appear in contrast with a study in a Brazilian population which showed that there was no significant association between the MTP -493G/T polymorphism and NAFLD, 20 as well as Marra who demonstrated that, the frequency of the G allele or of the G/G genotype for MTP was not different from that of controls without fatty liver. 38 …”
Section: Discussioncontrasting
confidence: 68%
“…Our finding is in agreement with Bernard et al; Hussain et al; Peng et al; Zheng et al; Miyaaki and Nakao who reported that MTP -493G/T polymorphism may be used for early detection of NAFLD. 16 , 12 , 2 , 36 , 37 This might appear in contrast with a study in a Brazilian population which showed that there was no significant association between the MTP -493G/T polymorphism and NAFLD, 20 as well as Marra who demonstrated that, the frequency of the G allele or of the G/G genotype for MTP was not different from that of controls without fatty liver. 38 …”
Section: Discussioncontrasting
confidence: 68%
“…The significant increase in serum glucose levels and the HOMA insulin resistance index at the end of treatment only in NAFLD patients with PNPLA3 G-allele is an intriguing finding. Perhaps, it may be due to an adverse effect of vitamin E supplementation (36) or an unknown interaction of this polymorphism with glucose metabolism. In our study, patients with the I148M PNPLA3 variant (G-allele carriers) had lower NASH resolution values.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the small sample size and the unicenter pilot study has limited the generalization of our results. Finally, our pilot study was only performed in Caucasians and ethnicity could be an unknown factor that influences this association (36).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from dietary models, there are multiple genetic mouse models used to mimic NAFL/NASH; such as, ob/ob mice (mutation in the leptin gene), db/db mice (mutation in the leptin receptor gene), and foz/foz mice (mutation in Alms1 gene, essential for primary ciliary function) 76 . In humans, there are certain genetic polymorphisms that are strongly associated with susceptibility to NAFL/NASH; such as, mutations in genes encoding for lipid metabolism, glucose metabolism, hypertension, or inflammation 77 . However, it is important to note that the genetic mouse models of NAFL/NASH do not overlap with these genetic polymorphisms.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%